The association between the activity profile and cardiovascular risk. Issue 8 (August 2016) - Maddison, Ralph; Jiang, Yannan; Foley, Louise; Scragg, Robert; Direito, Artur; Olds, Timothy
Abstract: Objectives: This study sought to better understand the interrelationships between physical activity and sedentary behaviour and the relationship to risk of cardiovascular disease (CVDR) in adults aged 30–75 years. Design: Cross-sectional. Methods: Data from two-year waves (2003–2004 and 2005–2006) of the National Health and Nutritional Examination survey were analysed in 2014. Accelerometer-derived time and proportion of time spent sedentary and on moderate-to-vigorous physical activity (MVPA) were calculated to generate four activity profiles based on cut-points to define low and high levels for the respective behaviours. Using health outcome data, CVDR was calculated for each person. Weighted multiple linear regression models were used to evaluate the predicted effects of sedentary and physical activity behaviours on the CVDR score, adjusting for participants' sex, age group, race, annual household income, and accelerometer wear time. Results: The lowest CVDR was observed among Busy Exercisers (high MVPA and low sedentary; 8.5%), whereas Couch Potatoes (low MVPA and high sedentary) had the highest (18.6%). Compared with the reference group (Busy Exercisers), the activity profile associated with the highest CVDR was Couch Potatoes (adjusted mean difference 3.6, SE 0.38, p < 0.0001). A smoothed three-dimensional response surface "risk landscape" was developed to better visualise the conjoint associations of MVPA and sedentary behaviour on CVDR for each activity profile. The association between MVPA was greater than that of sedentary behaviour; however, for people with low MVPA, shifts in sedentary behaviour may have the greatest impact on CVDR. Conclusions: Activity profiles that consider the interrelationships between physical activity and sedentary behaviour differ in terms of CVDR. Future interventions may need to be tailored to specific profiles and be dynamic enough to reflect change in the profile over time.